Climate - Hashmi, M. Z. U. R.; Bhatti, Muhammad Tousif; Azizi, M. A. (CAB International, 2023)
Climate change is a major threat in all the shared river basins in South Asia owing to the huge populations they sustain and the complex regional dynamics. This chapter summarizes the available knowledge related to changing climate trends in three Afghan–Pakistani transboundary river basins: the Kabul, Kurram and Gomal. A key finding indicates a consistent rise in temperature over the last 30 years. By the end of the 21st century, temperatures may rise by an additional 3–4°C under RCP1 4.5 and 5–6°C under RCP 8.5, relative to 2020 levels. The potential impact of temperature rise is compounded by considerable uncertainty associated with the current and future behaviour of precipitation in the three basins. The findings in this chapter will help practitioners and policymakers visualize the nature and scope of likely climate challenges in the three basins.